Interstitial Lung Disease in Werner Syndrome: A Case Report of a 55-Year-Old Male Patient. (16th December 2015) - Goletto, Tiphaine; Crockett, Flora; Aractingi, Selim; Toper, Cecile; Senet, Patricia; Cadranel, Jacques; Naccache, Jean-Marc
Abstract : Werner syndrome (WS) is a progeroid or premature aging syndrome characterized by early onset of age-related pathologies and cancer. The average life expectancy of affected people is 52.8 years and tends to increase. The major causes of death are malignancy and myocardial infarction. Increased telomere attrition and decay are thought to play a causative role in the clinical and pathological manifestations of the disease. Although telomere length, with or without germline mutation, is known to be associated with interstitial lung disease, the latter is not associated with WS. To the best of our knowledge, we report the first case describing a WS patient with fatal ILD. This case suggests that older patients with WS could develop ILD. Clinical outcome of WS patients may thus be improved by counselling them regarding smoking cessation or other exposure and by proposing antifibrotic therapy.